The song Kita Jaga Kita by UMP students on advise against COVID-19 - UMP, PNC (2020)
A group of students from Universiti Malaysia Pahang (UMP) made a remake of the song “Sakit” by Zynakal, changing its lyrics to advise Malaysians in the fight against the spread of the COVID-19 that has affected countries around the world, titled ‘Kita Jaga Kita’ (‘We Protect Each Other’).